An innovative educational media for reproductive health: The impact of the pillow t-shirt on knowledge among junior high school girl - Sari, Gita Nirmala; Ichwan, Erika Yulita; Aticeh; Munawarah, Raudhatul; Sukamti, Sri; Mulyana, Nana; Mulyati, Sri; Yamada, Eri (Universitas Aisyiyah Yogyakarta, 2025)
Enhancing reproductive health knowledge among adolescents is crucial to prevent unwanted pregnancies. This study aims to develop and evaluate the effectiveness of the